Thermal and Tensile Properties of Treated and Untreated Red Balau (Shorea Dipterocarpaceae) Filled LDPE Composites - Lafia-Araga, Ruth Anayimi; Hassan, Aziz; Yahya, Rosiyah (Journal of Science and Technology, 2011)
Red balau saw dust was heat-treated at 180°C and 200°C for one hour, extrusion compounded with Low Density Polyethylene (LDPE) at 20%, 40% and 60% volume fraction loadings and injection moulded. Thermal and tensile properties of the resultant composites were investigated as a function of filler loadings and treatment temperature. Increase in tensile moduli and decrease in tensile stress and strain were observed as filler loading and treatment temperature increased. Thermogravimetric analysis revealed an increase in degradation peak temperature of the composites from heat treated compared to the untreated wood composites. Differential scanning calorimetry revealed a decreasing trend in the degree of crystallinity (Xc) of the matrix when heat treated wood was used as filler. However, untreated wood showed an increase in Xc with increasing wood content.